2002
DOI: 10.1021/tx0155552
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dinitrobenzene Metabolism and GSH Depletion

Abstract: Previous work demonstrated that the mitochondrial fraction of rat seminiferous tubules is capable of metabolizing 1,3-dinitrobenzene, using NADPH as a cofactor. Moreover, 1,3-dinitrobenzene treatment of rat tubules caused a decrease in mitochondrial GSH levels. In situ mitochondrial metabolism of 1,3-dinitrobenzene may have caused this depletion through the production of reactive oxygen intermediates, generating oxidative stress and/or one or more metabolites of 1,3-dinitrobenzene which reacted nonenzymaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…3). Electron-deficient nitroaromatic compounds are known to be reduced in biological systems (Spain 1995) and to readily react with thiols (Ellis et al 1992) and also to covalently modify cysteine residues in proteins (Reeve et al 2002;Callan et al 2009). As the mutation of Cys387 in DprE1 leads to BTZ resistance, Trefzer et al (2010) speculated that the nitroso derivatives of BTZs form a semimercaptal with Cys387.…”
Section: Benzothiazinonesmentioning
confidence: 99%
“…3). Electron-deficient nitroaromatic compounds are known to be reduced in biological systems (Spain 1995) and to readily react with thiols (Ellis et al 1992) and also to covalently modify cysteine residues in proteins (Reeve et al 2002;Callan et al 2009). As the mutation of Cys387 in DprE1 leads to BTZ resistance, Trefzer et al (2010) speculated that the nitroso derivatives of BTZs form a semimercaptal with Cys387.…”
Section: Benzothiazinonesmentioning
confidence: 99%
“…In the final reduction step, the NPHA is converted to nitroaniline, by two electrons (Scheme ). Subsequent work by the same authors revealed that, nitrosonitrobenzene and NPHA nonenzymatically reacted with nonprotein sulfhydryls and mitochondrial glutathione (GSH), leading to GSH depletion and adduct formation with proteins (Reeve and Miller, ; Reeve et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The primary cellular targets of 1,3-DNB are Type 1 brainstem astrocytes, with secondary involvement of oligodendrocytes and neurons (Philbert et al, 1987). 1,3-DNB induced significant perturbations in metabolic function and increased ROS production within susceptible brainstem astrocytes (Romero et al, 1995, Tjalkens et al, 2000, Reeve et al, 2002, Romero et al, 1996). In in vitro models of neurotoxicity, 1,3-DNB exposure led to significantly increased levels of ROS, loss of the mitochondrial membrane potential (ΔΨ m ), ATP depletion, and onset of the MPT which preceded cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The resemblance between the lesions that result from exposure to 1,3-DNB and the regional distribution of lesions that develop in other acute energy deprivation syndromes suggests a common cellular pathogenic mechanism, at least in the early stages, that may result from oxidative stress-induced protein modification. Like other nitroaromatic chemicals, 1,3-DNB undergoes a nitroreductive metabolism that, in the presence of molecular oxygen, produces superoxide anion (Reeve et al, 2002, Tay et al, 2005). Additional intracellular sources of ROS, such as mitochondria, could conceivably increase the oxidative burden of a cell thus increasing the likelihood that protein damage may result from an oxidative mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation